Electrical anisotropy of conductive structures in Earth's crust of Red River fault Zone - Tuyến, Đoàn Văn; Toàn, Đinh Văn (Vietnam Journal of Earth Sciences, 2018)
Two tests for the electrical anisotropy hypothesisare introduced, evaluating the different features ofmagnetotelluric (MT) phases along measuredprofile. An analysis of MT field data on the line HoaSinh - Sac Ninh crossing Red River Fault Zone(RRFZ) Jets us devide five conductive structures atdepth varying from 0.5 to 80 km. Only deeper onefrom them is indicating high electrical anisotropymay be related to the evidence of Lithosphereactivity beneath RRFZ. Other structures are isotropicdistributing in the crust out site RRFZ related to highconductive mineral and hot water sources.